Macroevolutionary effects on primate trophic evolution and their implications for reconstructing primate origins. Issue 133 (August 2019) - Scott, Jeremiah E.
Abstract: The visual-predation hypothesis proposes that certain derived features shared by crown primates reflect an insectivorous ancestry. Critics of this idea have argued that because insectivory is uncommon among extant primates it is unlikely to have been a major influence on early primate evolution. According to this perspective, the low frequency of insectivory indicates that it is an apomorphic deviation from the mostly conserved primate ecological pattern of herbivory. The present study tests two alternative hypotheses that are compatible with an insectivorous ancestor: (1) that trophic evolution was biased, such that herbivory evolved repeatedly with few shifts back to insectivory, and (2) that insectivorous lineages have diversified at a lower rate than herbivorous lineages owing to differential trophic effects on speciation and extinction probabilities. Model-based analysis conducted using trait data for 307 extant primate species indicates that rates of transition into and out of insectivory are similar, rejecting the hypothesis of biased trophic evolution. On the other hand, the hypothesis of asymmetric diversification is supported, with insectivorous lineages having a lower rate of diversification than herbivorous lineages. This correlation is mediated by activity pattern: insectivory occurs mostly in nocturnal lineages, which have a lower diversification rate than diurnal lineages. The frequency of insectivory also appears to have been shaped by repeated transitions into ecological contexts in which insectivory is absent (large body size) or rare (diurnality). These findings suggest that the current distribution of trophic strategies among extant primates is the result of macroevolutionary processes that have favored the proliferation and persistence of herbivory relative to insectivory. This conclusion implies that the low frequency of insectivory is not necessarily evidence against the visual-predation hypothesis.